CIVIL SOCIETY AND REGIONAL POWERS IN A CHANGING WORLD: THE CASES OF BRAZIL AND INDIA - Secches, Daniela Vieira; Aires, Maria Cristina Andrade (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
A changing world in which global and regional powers rethink their actions and preferences in the international arena is a world where domestic politics increasingly creates a more complex framework for foreign behavior. Many newly emerging powers have just recently adopted a democratic regime, while others are still governed by hard autocracies. Within this context, their civil societies have different channels to express their preferences towards the new world order under formation and their expectations concerning how their states plan to be part of it. This paper will discuss how emerging regional powers behave in this changing world, the possibilities and limits imposed by civil society pressure, or even inaction. The authors wish to address how these systemic changes impact on the channels through which civil society movements voice their platforms for their country international role, considering the degree of democratic institutional consolidation as an intervening variable. As case studies, this theoretical debate will be applied to contemporary Brazil and India.